2020
DOI: 10.3390/en13030614
|View full text |Cite
|
Sign up to set email alerts
|

LAEND: A Model for Multi-Objective Investment Optimisation of Residential Quarters Considering Costs and Environmental Impacts

Abstract: Renewable energy systems are especially challenging both in terms of planning and operation. Energy system models that take into account not only the costs but also a wide range of environmental impacts support holistic planning. In this way, burden-shifting caused by greenhouse gas mitigation can be identified and minimised at an early stage. The Life cycle Assessment based ENergy Decision support tool LAEND combines a multi-criteria optimising tool for energy system modelling and an integrated environmental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Legal criteria X 5,1 planning documents for the power line X 5,2 planning documents for the investment area X 5, 3 the environmental decision for the power line X 5, 4 the environmental decision for the investment area…”
Section: Symbolmentioning
confidence: 99%
See 1 more Smart Citation
“…Legal criteria X 5,1 planning documents for the power line X 5,2 planning documents for the investment area X 5, 3 the environmental decision for the power line X 5, 4 the environmental decision for the investment area…”
Section: Symbolmentioning
confidence: 99%
“…Growing concerns about the impact of the power system on the environment and depletion of non-renewable energy resources, as well as the growing public interest in the energy sector in general, have resulted in the inclusion of ecological and social aspects in the power system development planning. Considerations on the impact of energy fuels on the environment are currently being undertaken in the scientific literature [4].…”
Section: Introductionmentioning
confidence: 99%
“…Impacts also shift from the use phase to the construction phase. [4], [5] Considering more environmental aspects besides the usual techno-economic aspects requires a multiobjective optimization of energy systems. In this study, this is achieved by combining an ESM with a life cycle assessment (LCA) of energy conversion technologies.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies highlight the importance of integrating LCA data into ESMs and considering the entire range of efficient solutions, for example García-Gusano et al, Rauner & Budzinsiki [7], Tietze et al [5], Xu et al [8] or Junne et. al [9].…”
Section: Introductionmentioning
confidence: 99%
“…Applying multi-objective optimization, the authors showed that an environmentally sustainable system leads to increased deployment of VRE, particularly wind energy, compared to an unconstrained cost-optimal system based mainly on fossil fuels. Multi-objective optimization integrating costs and life cycle impacts was conducted by Tietze et al [17] and applied to an exemplary residential quarter. In several model runs that considered different impacts, the authors showed a number of different system configurations resulting from different weightings of environmental impacts and highlighted the importance of including the life cycle perspective in the design of energy systems.…”
Section: Introductionmentioning
confidence: 99%